IDENTIFIKASI SISTEM KEBERHASILAN KEWIRAUSAHAAN MAHASISWA MELALUI PENDEKATAN SISTEM - Sulistyadi, Kohar (JURNAL TALENTA PSIKOLOGI, 2013)
As the employment opportunities in the business industries that the harder lead to increased unemployment. For this case the University needs to identify systems that haveachieved success entrepreneurs as input lecturer in entrepreneurship development program in an effort to equip the students in creating employment. Some actors and the role of entrepreneurship students need to be identified in order to formulate the concept of entrepreneurial success. Subsequently followed up with a decentexample riel applied to target entrepreneurial business benefits. Results of studies on the identification of the system's success can be the formulation of student entrepreneurship development programs implemented suggestions paqra lecturer at the University of Sahid